Analysis of the Status and Influencing Factors of Online Learning - He, Jiaju; Zhao, Hong; Jiang, Fei (Canadian Journal of Learning and Technology / Revue canadienne de l’apprentissage et de la technologie, 2022)
During the COVID-19 prevention and control period, large-scale online education was the largest digital transformation practice in education in human history. This study launched a questionnaire survey on primary and high school students. The survey was conducted from four aspects: demographics, online learning preparation, the online learning situations, and online learning experience. This study thoroughly investigated the status and problems of students’ online learning and analysed the characteristics of students’ online learning and the differences amongst grades. The study found that students have high adaptability and continuance intention to online learning. This study found that students also had some learning difficulties in the process of online learning, mainly manifested by lack of interaction, difficulty in concentration, and lack of learning initiative. There were significant differences among different grades. The overall situation of junior high school students’ online learning is better than that of primary school students and senior high school students.